Philosophy of Behavioral Biology
VIII, 376 p.
Keywords: This volume provides a broad overview of issues in the philosophy of behavioral biology, covering four main themes: genetic, developmental, evolutionary, and neurobiological explanations of behavior. It is both interdisciplinary and empirically informed in its approach, addressing philosophical issues that arise from recent scientific findings in biological research on human and non-human animal behavior. Accordingly, it includes papers by professional philosophers and philosophers of science, as well as practicing scientists. Much of the work in this volume builds on presentations given at the international conference, “Biological Explanations of Behavior: Philosophical Perspectives”, held in 2008 at the Leibniz Universität Hannover in Germany. The volume is intended to be of interest to a broad range of audiences, which includes philosophers (e.g., philosophers of mind, philosophers of biology, and metaethicists), as well as practicing scientists, such as biologists or psychologists whose interests relate to biological explanations of behavior. .